ANALISIS PELANGGARAN KODE ETIK ADVOKAT HOTMAN PARIS TERHADAP JHONNY ANDREAN - Rabawati, Dwytias Witarti; Anrolan Hello, Grendi; Anastasia Wijono, Maria; Konstantinus Soo, Yakobus; Mario Pignateli Milo, Derryl Yosef; Biola Tukan, Christian Andryan; Oshinta Joni, Maria Hilary; Oscar Elu, Januario (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
The "Jhony Coffee Case" case which occurred in 2023 involved Hotman Paris as PT’s attorney. Jhony Coffee in questioning the trademark with Johnny Andrean. During this legal process, Hotman Paris issued a controversial statement calling Johnny Andrean a "plagiarist" and a "thief", which sparked criticism from various groups, including advocates. This statement is considered to violate the advocate’s code of ethics, in particular Article 4 letter (b) of the Indonesian Advocate’s Code of Ethics, which includes statements that are insulting or defamatory of another party. Realizing the impact of his statement, Hotman Paris then apologized, admitted his mistake, and emphasized that he had no intention of insulting Johnny Andrean. This case reflects the